Effect of ski boot rear stiffness (SBRS) on maximal ACL force during injury prone landing movements in alpine ski racing: A study with a musculoskeletal simulation model - Eberle, R.; Heinrich, D.; Kaps, P.; Oberguggenberger, M.; Nachbauer, W. (Journal of Sports Sciences, 2017)
A common anterior cruciate ligament (ACL) injury situation in alpine ski racing is landing back-weighted after a jump. Simulated back-weighted landing situations showed higher ACL-injury risk for increasing ski boot rear stiffness (SBRS) without considering muscles. It is well known that muscle forces affect ACL tensile forces during landing. The purpose of this study is to investigate the effect of different SBRS on the maximal ACL tensile forces during injury prone landings considering muscle forces by a two-dimensional musculoskeletal simulation model. Injury prone situations for ACL-injuries were generated by the musculoskeletal simulation model using measured kinematics of a non-injury situation and the method of Monte Carlo simulation. Subsequently, the SBRS was varied for injury prone landings. The maximal ACL tensile forces and contributing factors to the ACL forces were compared for the different SBRS. In the injury prone landings the maximal ACL tensile forces increased with increasing SBRS. It was found that the higher maximal ACL force was caused by higher forces acting on the tibia by the boot and by higher quadriceps muscle forces both due to the higher SBRS. Practical experience suggested that the reduction of SBRS is not accepted by ski racers due to performance reasons. Thus, preventive measures may concentrate on the reduction of the quadriceps muscle force during impact.